2019
DOI: 10.3390/membranes9120162
|View full text |Cite
|
Sign up to set email alerts
|

Insignificant Impact of Chemotactic Responses of Pseudomonas aeruginosa on the Bacterial Attachment to Organic Pre-Conditioned RO Membranes

Abstract: We investigated the impact of conditioning compositions on the way bacteria move and adhere to reverse osmosis (RO) membranes that have been pre-conditioned by organic compounds. We used humic acid (HA), bovine serum albumin (BSA), and sodium alginate (SA) to simulate conditioning layers on the RO membranes. First, we investigated the chemotactic responses of Pseudomonas aeruginosa PAO1 to the organic substances and the impact of changes in physicochemical characteristics of pre-conditioned membranes on bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…The positive impact of the surface roughness on bacterial adhesion has been demonstrated in several studies although the reported outcomes remain contradictory and are shown to be dependent on the bacterial species as well as on the experimental conditions. 58–61…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive impact of the surface roughness on bacterial adhesion has been demonstrated in several studies although the reported outcomes remain contradictory and are shown to be dependent on the bacterial species as well as on the experimental conditions. 58–61…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of the surface roughness on bacterial adhesion has been demonstrated in several studies although the reported outcomes remain contradictory and are shown to be dependent on the bacterial species as well as on the experimental conditions. [58][59][60][61] Concerning the PF-QNM surface topography of P. aeruginosa PAO1-Tn7-gfp adhered to the SiO 2 surface conditioned with a BSA layer, resulting from a solution with a protein concentration of 10.0 µM, the bacteria display a tendency to burrow into the BSA layer, thus modifying its local organization and rendering the bacterial flagella undiscernible in the contrary to the BSA layer obtained from solution with a lower protein concentration (0.75 µM) (Fig. 7b and c).…”
Section: Biomaterials Science Papermentioning
confidence: 99%